Metallogeny and its link to orogenic style during the Nuna supercontinent cycle - Pehrsson, S.; Eglington, B.; Evans, D.; Huston, D.; Reddy, Steven (2016)
© 2016 The Geological Society of London. The link between observed episodicity in ore deposit formation and preservation and the supercontinent cycle is well established, but this general framework has not, however, been able to explain a lack of deposits associated with some accretionary orogens during specific periods of Earth history. Here we show that there are intriguing correlations between styles of orogenesis and specific mineral deposit types, in the context of the Nuna supercontinent cycle. Using animated global reconstructions of Nuna's assembly and initial breakup, and integrating extensive databases of mineral deposits, stratigraphy, geochronology and palaeomagnetism we are able to assess spatial patterns of deposit formation and preservation. We find that lode gold, volcanic-hosted-massive-sulphide and nickel-copper deposits peak during closure of Nuna's interior ocean but decline during subsequent peripheral orogenesis, suggesting that accretionary style is also important. Deposits such as intrusion-related gold, carbonate-hosted lead-zinc and unconformity uranium deposits are associated with the post-assembly, peripheral orogenic phase. These observations imply that the use of plate reconstructions to assess orogenic style, although challenging for the Precambrian, can be a powerful tool for mineral exploration targeting. Supplementary material including (1) tables (S1-S3) of Euler poles and palaeopoles used, summary of Nuna orogens; (2) a figure (S1) of modelled plate velocities; (3) mp4 files (S1 & S2) of the model with age data; ore deposits and VGPs; and (4) a zip file (S1) of the Gplates model is available at http://www.geolsoc.org.uk/SUP18822.